2021
DOI: 10.1111/jfpp.16194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green tea (Camellia sinensis) and guava (Psidium guajava) extracts on the quality of snakehead (Channa striata) fillets during ice storage

Abstract: The antioxidant and antimicrobial properties of Camellia sinensis and Psidium guajava leaf extracts were determined and applied as soaking solutions for snakehead (Channa striata) fillets prior to 12‐day ice storage. The scavenge 50% of the DPPH (2,2ʹ‐diphenyl‐1‐picrylhydrazyl) free radicals (IC50) of C. sinensis was 7.63 µg/mL and 5.04 µg/mL for P. guajava extract. The minimum inhibition concentrations (MIC) of C. sinensis and P. guajava against Aeromonas hydrophila were 625 and 313 µg/mL, respectively. The I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 98 publications
1
4
0
Order By: Relevance
“…The third factor is the antimicrobial activity of the phenolic compounds. Microbial activity extends the shelf life of tempehs (11). Similar results were also found in a study by Pakfetrat et al (39), which explained that applying tea extract could reduce the initial microbial load on legumes and extend their shelf life.…”
Section: Shelf-life Of Extract Tea-treated Tempehsupporting
confidence: 85%
See 1 more Smart Citation
“…The third factor is the antimicrobial activity of the phenolic compounds. Microbial activity extends the shelf life of tempehs (11). Similar results were also found in a study by Pakfetrat et al (39), which explained that applying tea extract could reduce the initial microbial load on legumes and extend their shelf life.…”
Section: Shelf-life Of Extract Tea-treated Tempehsupporting
confidence: 85%
“…However, this technology is expensive, making it difficult to apply to tempeh artisans in Indonesia. The submersion of tempeh with tea extract can be utilized to extend the shelf life of tempeh because it has been proven to increase the shelf life of other food products (9)(10)(11). The polyphenol components of tea have antioxidant and antimicrobial properties (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that seafood spoiled recorded on flavors that are very fishy, rotten, and putrid. One of the most crucial factors for consumers is the color of the fish and fish products since it denotes the quality and is linked to the flavor and freshness of seafood (Huynh et al 2022). Kenawi and Abdelaal (2021) revealed that comparison to the control, the color, taste, odor, texture, and general acceptance scores improved with the addition of 1% moringa leaves powder.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan is very important as an amino acid compound that provides feelings of comfort, pleasure and reduces stress [68,69]. Tryptophan helps in weight loss and sleep disorders [47].…”
Section: Identification Of Non-volatile Flavor Compounds Of Snakehead...mentioning
confidence: 99%